2015
DOI: 10.4028/www.scientific.net/kem.656-657.101
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Possibilities and Limits for Producer Gas Desulfurization and HCL Related Interferences for Zn, Mn, Ce and La Based Sorbents of Sulfur Compounds

Abstract: The study is concentrated on thermodynamic analyses of gas desulfurization process (deep removal of H2S, COS, thiophene) by selected solid sorbents (ZnO, MnO, CexOy and La2O3) and on interferences caused by presence of hydrogen halides in a temperature range 500-1100 K. The results show that theoretically Ce2O3 and La2O3 are the best sorbents for sulfur compounds at temperatures over approx. 700 K. The CexOy, La2O3 and MnO based sorbents can suffer from significant interferences caused by higher concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Throughout the literature, most reports on dry dechlorination adsorbents have been explored at a high temperature, and the reaction rates of alkaline earth oxides with HCl are strongly dependent upon the reaction temperature. Yan et al indicated that the utilization rate of calcium hydroxide was less than 15% when the experimental temperature was reduced to 170 °C, which was mainly due to the poor reaction activity and low porosity of the active component. In the past decade, with the extensive research of porous materials, such as activated carbon, molecular sieve, activated alumina, etc., mesoporous substrate-supported active components has been recognized as the most potential candidate for acid gas adsorption and separation. Moreover, to further improve the structural properties and low-temperature reactivity, transition metal oxides were employed as the main active components in some studies. However, as a result of the lower solubility product constant ( K sp ) of metal sulfides, H 2 S tends to combine with these transition metal ions first, resulting in the poisoning deactivation of the adsorbent. In addition, the dense acid species salts formed by carbonation and sulfurization also increase the mass transfer and diffusion resistance of HCl. In view of the above, as a result of poor HCl adsorption selectivity and high cost, these sorbents are far away from industrial practice application. , Up to now, there is a lack of research on high-efficiency selective dechlorination under a low-temperature and complex gas environment …”
Section: Introductionmentioning
confidence: 99%
“…Throughout the literature, most reports on dry dechlorination adsorbents have been explored at a high temperature, and the reaction rates of alkaline earth oxides with HCl are strongly dependent upon the reaction temperature. Yan et al indicated that the utilization rate of calcium hydroxide was less than 15% when the experimental temperature was reduced to 170 °C, which was mainly due to the poor reaction activity and low porosity of the active component. In the past decade, with the extensive research of porous materials, such as activated carbon, molecular sieve, activated alumina, etc., mesoporous substrate-supported active components has been recognized as the most potential candidate for acid gas adsorption and separation. Moreover, to further improve the structural properties and low-temperature reactivity, transition metal oxides were employed as the main active components in some studies. However, as a result of the lower solubility product constant ( K sp ) of metal sulfides, H 2 S tends to combine with these transition metal ions first, resulting in the poisoning deactivation of the adsorbent. In addition, the dense acid species salts formed by carbonation and sulfurization also increase the mass transfer and diffusion resistance of HCl. In view of the above, as a result of poor HCl adsorption selectivity and high cost, these sorbents are far away from industrial practice application. , Up to now, there is a lack of research on high-efficiency selective dechlorination under a low-temperature and complex gas environment …”
Section: Introductionmentioning
confidence: 99%